Clinical efficacy of hydroxyapatite toothpaste containing Polyol Germanium Complex (PGC) with threonine in the treatment of dentine hypersensitivity - Natalia Vlasova; Vadim Samusenkov; Irina Novikova; Denis Nikolenko; Nikita Nikolashvili; Ilana Gor; Anna Danilina (Saudi Dental Journal)
Introduction: This study aims to evaluate the clinical efficacy of a hydroxyapatite toothpaste containing a Polyol Germanium Complex with threonine in treating dentine hypersensitivity. The study also seeks to monitor the quality of life of the treated dentine hypersensitivity sufferers. Materials and methods: This study is a randomized clinical trial with a total of 120 patients with dentine hypersensitivity. All participants were divided into three groups: patients assigned to the GARDA SILK toothpaste; patients receiving the conventional fluoride toothpaste for comparison purposes, and patients asked to brush their teeth without toothpaste. The modified Quigley-Heine Plaque Index was assessed at the baseline and after treatment. Sensitivity was assessed at baseline, 3, 7 and 14 days using the air stimulus (Schiff Index). The impact of dentine hypersensitivity on the quality of life was assessed before and after the treatment with the Russian version of the Dentine Hypersensitivity Experience Questionnaire (DHEQ). Results: After 14 days of treatment, the mean Plaque Index scores in Groups 1 and 2 did not exceed 1 and averaged 0.72 ± 0.249 and 0.86 ± 0.213, respectively. In Group 3, the mean Plaque Index was significantly higher (1.04 ± 0.070, p < 0.05). The mean Schiff sensitivity scores in Group 1 decreased to 2.45 ± 0.42 at 3 days, 1.84 ± 0.26 at 7 days, and 1.02 ± 0.34 at 14 days. Group 2 exhibited smaller reductions in the Schiff index at all time points. In this group, Schiff scores dropped to 2.67 ± 0.28 after 3 days, 2.34 ± 0.44 after 7 days, and 1.93 ± 0.36 after 14 days. Conclusion: The GARDA SILK hydroxyapatite toothpaste with a threonine-containing Polyol Germanium Complex (PGC) is effective in maintaining good oral hygiene, reducing dentine hypersensitivity, and improving the quality of life of dentine hypersensitivity sufferers.